A second life ; Life beneath the rubble ; Hidden victims [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
A visit of Probe Team Productions after a year to the places and people affected by the earthquake in July 1990.
A second life (20 min.) -- Life beneath the rubble (20 min.) -- Hidden victims (15 min.)
VHS.
Host, Cheche Lazaro ; Reporter, Luchi Cruz-Valdes.
Keywords: Earthquakes -- Philippines -- Baguio City; Disaster victims -- Philippines; Earthquakes -- Philippines -- Cabanatuan City; Earthquakes -- Philippines -- Dagupan City; Earthquakes -- Philippines -- La Union